Konsep Kepemilikan dalam Islam sebagai Pondasi Terciptanya Green Economy di Era Modern - Yunilhamri, Muhammad Syauqi; Mawardi, Mawardi (Al-Maqashid: Journal of Economics and Islamic Business, 2025)
This article explores the relationship between the Islamic concept of ownership and the implementation of green economy principles in the modern era. In Islam, ownership is not an absolute individual right but a trust (amanah) that must be managed responsibly, emphasizing the welfare of the community and environmental sustainability. This aligns with the green economy's focus on environmental sustainability and social justice. By analyzing QS. Al-Baqarah: 188 and QS. An-Nur: 33, the article highlights how these verses advocate for the responsible management of natural resources without causing harm to the earth, prioritizing sustainability. Additionally, the concept of maqashid al-shariah, which emphasizes the protection of wealth and life, serves as a foundation for the implementation of green economy principles. Wise management of natural resources, as advocated in Islam, can provide a robust framework for fostering a sustainable economy. By integrating Islamic principles into resource management, a green economy rooted in Islamic values offers an alternative to achieving sustainable prosperity for humanity and environmental preservation for future generations.